Synthesis and Photocatalytic Degradation of Dimer Model Compounds of Lignin Over UV Irradiated Ti - Murali Krishna, M.P.S.; Moses, G.S.; Murali Krishna, K.V.S.G. (Asian Journal of Chemistry, 2010)
The effluents of paper mill contain lignin as major constituent. Lignin is a bio polymer and it has less affinity to undergo biodegradation, therefore it persists in water. Model dimer compounds synthesized from coniferyl alcohol, p-coumrylic acid and sinapyl alcohol. The epoxides of respective alcohols are obtained by m-chloroperbenzoic acid oxidation on double bonds. In presence of sodium hydroxide the epoxides are refluxed with coniferyl alcohol, p-coumrylic acid and sinapyl alcohol, respectively so that dimers are formed. The reaction products are isolated by flash chromatography. Here an attempt has been made to subject photocatalysis of model compounds using aqueous TiO2 suspension. For the experimental setup fabricated, the optimum mass of catalyst and pH of aqueous media suitable for optimum possible degradation was investigated. Initially, the absorption characteristics of model compounds prepared are determined. The influence of the nature of phenolic units on photo degradation has been investigated by comparing the initial degradation rates. The Langmuir-Hinshelwood kinetics constant parameters evaluated. Kinetics of chemical oxygen demand and phenolic contents studied and based on the results path of degradation proposed.